Instytucja sprostowania świadectwa pracy po wejściu w życie nowelizacji z dnia 16 maja 2019 roku - Duraj, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The following article aims to assess the amendment to the provisions governing the institution of the correction of the employment record. The primary objective of the changes introduced in 2019 was to adopt solutions that will make it easier for employees to exercise their rights to obtain arecord of their employment from their employer and to correct its content. The legislator extended the time limits for correcting the record of employment at the request of the employee and clarified the situation of the employee, whom the employer did not notify of the refusal to correct their record of employment. The author focuses particular attention on the additional claims which the legislator has granted the employee to the labour court related to the correction of the record of employment. The first concerns the employer’s obligation to correct the record of employment in a situation where he or she evades this obligation, and the second concerns the determination of the right to correct the record of employment in cases where the employer does not exist or for other reasons correcting the employment certificate is impossible. The amendment of 16 May 2019 introduced non-procedural proceedings into the legal order in matters related to labour law as well as in the field of correcting employment records.
Keywords: record of employment; correction of the employment record; separate proceedings before labour court; labour law cases; an employee; an employer